Free internet access as a human right - Reglitz, Merten (Cambridge University Press, 2024)
"Merten Reglitz makes a case for a new human right to free Internet access, arguing it is crucial for protecting and advancing fundamental moral interests. He examines the risks the Internet poses to our most important rights if it is not safeguarded by public institutions"--